2010
DOI: 10.1111/j.1398-9995.2009.02218.x
|View full text |Cite
|
Sign up to set email alerts
|

Allergen provocation increases TH2‐cytokines and FOXP3 expression in the asthmatic lung

Abstract: Despite an increase in CD4(+)CD25(bright) cells expressing high levels of FOXP3 in response to bronchial allergen provocation, asthmatic patients exhibit enhanced levels of Th2 cytokines in the lung, which may indicate an inability among infiltrating cells to suppress Th2 responses.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

7
65
2

Year Published

2011
2011
2020
2020

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 58 publications
(74 citation statements)
references
References 36 publications
7
65
2
Order By: Relevance
“…In particular, GATA3 expression was positively correlated with pSTAT6, which indicated a certain regulatory relationship between pSTAT6 and GATA3. As we know, pSTAT6 can be regulated by many factors in the body and change in pSTAT6 correlates with many diseases (Batra et al, 2004;Thunberg et al, 2010;Chen et al, 2013;Yao et al, 2013;Irvin et al, 2014). Our present results prove that after boswellic acid treatment, GATA3 is downregulated following a decrease in pSTAT6, which indicates that boswellic acid may improve the asthma phenotype by inhibiting pSTAT6 and thus influencing GATA3 expression (Tachdjian et al, 2010).…”
Section: Discussionsupporting
confidence: 69%
“…In particular, GATA3 expression was positively correlated with pSTAT6, which indicated a certain regulatory relationship between pSTAT6 and GATA3. As we know, pSTAT6 can be regulated by many factors in the body and change in pSTAT6 correlates with many diseases (Batra et al, 2004;Thunberg et al, 2010;Chen et al, 2013;Yao et al, 2013;Irvin et al, 2014). Our present results prove that after boswellic acid treatment, GATA3 is downregulated following a decrease in pSTAT6, which indicates that boswellic acid may improve the asthma phenotype by inhibiting pSTAT6 and thus influencing GATA3 expression (Tachdjian et al, 2010).…”
Section: Discussionsupporting
confidence: 69%
“…Allergic responses in the lung are traditionally thought of as being Th2 mediated; however, recent studies have shown that IL-9 contributes to allergic responses by promoting mast cell expansion and production of IL-13, which stimulates the release of mucus and contributes to airway hyperresponsiveness (1,5,8,9). Serum IL-9 levels, which correlate with symptom severity in patients with allergic rhinitis, depend on exposure to a causal allergen (10)(11)(12)(13)(14). Similarly, during the effector phase of food allergy, IL-9 promotes mastocytosis, which increases intestinal permeability (15).…”
mentioning
confidence: 99%
“…Uncontrolled effector T cell responses may result in excessive inflammation and, eventually, in host pathology. In this regard, Th1 and Th17 cells have been associated with various human autoimmune conditions, such as multiple sclerosis (1) and inflammatory bowel disease (2), whereas Th2 cells have been implicated in the development of human allergic asthma (3). Given that CD4 + T cells not only play a key role in protecting the organism from various threats but are also potentially harmful to self-tissues, their function needs to be under stringent control.…”
mentioning
confidence: 99%